Predictive Value of Early Amplitude Integrated EEG in Extremely Premature Infants. (October 2020) - Richardson, Justin; Goshen, Sharon; Meledin, Irina; Golan, Agneta; Goldstein, Ester; Shany, Eilon
Amplitude integrated EEG (aEEG) is increasingly utilized in preterm infants. The aim of the study was to evaluate whether semiquantitative visual assessment of aEEG background during the first 72 hours of life is associated with long-term outcome in a group of premature infants born less than 28 weeks' gestation. Infants were prospectively enrolled and monitored in the first 72 hours after birth. aEEG was classified daily according to background activity, appearance of cyclical activity and presence of seizures activity. Log-rank and multivariable cox analysis were used to explore associations of background aEEG activity with short and long-term outcome. Overall, 51 infants were enrolled into the study. Depressed aEEG background on the third day of life was associated with poor outcome ( P = .028). Similarly, absence of cycling on the third day of life was associated with death or poor outcome ( P = .004 and .012, respectively). In different multivariable models adjusted for gestational age, severe intraventricular hemorrhage or use of sedative medication, neither background nor cycling activities were associated with outcome. Depressed aEEG background and absence of aEEG cycling on the third day of life are associated with poor outcome in univariable analysis. Although continuous aEEG monitoring of premature infants can provide real-time assessment of cerebral function, its use as a predictive tool for long-term outcome using visual analysis requires caution as its predictive power is not greater than that of gestational age or intraventricular hemorrhage.